Pembuatan Tracer Elektronik Berbasis Web di Puskesmas Semboro Jember - Nur Faiza Hardiyanti; Niyalatul Muna; Atma Deharja; Muhammad Yunus (Indonesian Journal Publisher, 2025)
The activity of borrowing and returning medical records at the Semboro Jember Community Health Center experienced several obstacles, including the failure to implement a tracer to mark files that would leave the storage room, and the recording of borrowing and returns was still carried out manually in the expedition book. The aim of this research is to design a website-based electronic tracer system. The system development method uses waterfall. The result of this research is the creation of a website-based electronic tracer which has advantages including that police officers as loan officers can borrow medical record files by looking at the patient's name or medical record number to be borrowed and can print an electronic tracer accompanied by a QR Code to be handed over to the officer. medical record filling section. Meanwhile, medical record officers can add patient data, officer data, doctor data and verify the return of files that have been returned by police officers or loan officers, return notifications and late charts. The results of testing carried out on all features and forms are that they run well and meet user needss